Management of patients who are at risk of violent behaviour: A case study report - Prasetya, Denni; Apriliyani, Ita (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Risk of Violent Behavior is a manifestation of uncontrolled anger, which can cause harm to oneself, others, and the environment, both physically, emotionally, and sexually. This problem has to do with a strong range of emotions, in which anger arises in response to situations that offend self-esteem, unmet needs, or expectations that do not correspond to reality. Purpose: To explain the management of patients at risk of violent behavior. Method: A case study with stages of study, diagnosis, intervention, implementation, and evaluation for 4 days. The intervention focused on the implementation of Implementation Strategies (SP) 1-4, including deep breathing relaxation techniques and pillow beating, medication adherence, assertive communication, and spiritual approaches. Results: The results showed an improvement in self-control skills, a decrease in anger intensity, and emotional stability in patients. Conclusion: SP 1-4 interventions have been shown to be effective in reducing the risk of violent behavior so that the problem of violent behavior risk can be resolved. Keywords: Nursing Intervention; Risk of Violent Behavior; Self-Control Skills.